The Influence of Company Size and Debt Ratio on the Financial Performance of Bank Subsector Companies Listed on the Indonesian Stock Exchange (IDX) in 2020-2023 - Mursalini, Wahyu Indah; Nurhayati, Nurhayati; Budiman, Harry (CV. Proaksara Global Transeduka, 2025)
This research analyzes how Company Size and Debt Ratio affect the Financial Performance of banking subsector companies listed on the Indonesia Stock Exchange from 2020 to 2023. Using quantitative regression analysis on financial statement data, the study employed purposive sampling to select 36 banking companies meeting the research criteria. The findings reveal that Company Size significantly and positively influences Financial Performance, with a t-value of 2.425 exceeding the t-table value of 1.987 and significance of 0.017 below 0.05, confirming hypothesis H1. Conversely, Debt Ratio shows no significant individual effect on Financial Performance, with a t-value of -1.410 below 1.987 and significance of 0.162 above 0.05, rejecting hypothesis H2. However, simultaneous testing demonstrates that Company Size and Debt Ratio together significantly affect Financial Performance, with an f-value of 3.612 surpassing f-table value of 3.103 and significance of 0.031 below 0.05, accepting hypothesis H?. The study concludes that Company Size plays a crucial role in enhancing banking sector financial performance, indicating that larger banks tend to achieve better financial outcomes. While Debt Ratio lacks individual significance, suggesting that debt levels alone do not meaningfully impact performance, the combined effect of both variables proves statistically significant. This suggests that when analyzed collectively, Company Size and Debt Ratio contribute to explaining variations in banking financial performance, though Company Size emerges as the more influential factor among Indonesian banking companies during the examined period.